Participatory, human-centered, equitable, neurodiverse, and inclusive XR: Co-design of extended reality with autistic users - Schmidt, Matthew; Lu, Jie; Huang, Rui; Francois, Marc-Sonley; Lee, Minyoung; Wang, Xiaoman; Feijoo-Garcia, Pedro Guillermo (Educational Technology ＆ Society, 2024)
Extended reality (XR) such as Virtual Reality (VR) and Augmented Reality (AR) has been heralded as a particularly promising technology for autistic people. However, prior studies have centered around curing or ameliorating deficits and impairments and are typically conducted by non-disabled and non-autistic researchers. Using co-design and a variety of learning experience design methods and processes, Project PHoENIX (Participatory, Human-centered, Equitable, Neurodiverse, and Inclusive XR) speaks to the need for research that applies a social-ecological perspective to the design and evaluation of VR experiences for autistic users, with the goal of decreasing environmental barriers and promoting a more inclusive society. In this study, we describe a multi-cycle process of educational design research (EDR), consisting of iterative human-centered formative design, development, implementation, and evaluation of Project PHoENIX from Spring 2021 to Spring 2022. A framework for conducting co-design and collaborative educational design research with autistic individuals in a VR environment is provided along with design principles that support this framework. Findings from 3 meso-cycles illustrate the dual outcomes of educational design research, namely, (1) a consistently maturing intervention and (2) improving theoretical understanding. Findings underscore the feasibility of our approach, and demonstrate potential to scale.